Aberrant brain structural large-scale connectome in Crohn's disease - Thomann, Anne K.; Reindl, Wolfgang; Wüstenberg, Torsten; Kmuche, Dagny; Ebert, Matthias; Szabo, Kristina; Wolf, Robert Christian; Hirjak, Dusan; Niesler, Beate; Griebe, Martin; Thomann, Philipp (Neurogastroenterology and motility, 2019)
Background Disturbed brain-gut interactions and a bidirectional relationship between inflammation and psychiatric symptoms such as anxiety and depression are being discussed in patients with inflammatory bowel diseases (IBD). Alterations of brain structure and function in IBD have been reported with heterogeneous results. Whether these changes reflect independent localized deficits or rather a systematic disruption in the anatomical organization of large-scale brain networks remains unclear. The present study investigated the gray matter structural connectome in patients with Crohn's disease (CD). Methods Sixty participants (30 with quiescent CD and 30 matched healthy controls [HC]) underwent high-resolution brain MRI at 3 Tesla. Well-established graph theoretical metrics were analyzed at the global and regional network level and compared between groups. Key Results The networks in both groups followed a small-world organization, that is, an architecture that is simultaneously highly segregated and integrated. However, transitivity, a measure of global network segregation, was significantly reduced in patients (P = 0.003). Regionally, patients showed a reduction of nodal betweenness centrality in the right insula and cuneus and the left superior frontal cortex and reduced nodal degree within the left-hemispheric cingulate and the left lateral and right medial orbitofrontal cortex. Conclusion and Inferences These findings lend support to the hypothesis that CD is accompanied by alterations in both global network organization and regional connectivity. A deeper understanding of neural central networks in IBD may facilitate the development of complementary strategies in the treatment of "extraintestinal" comorbid conditions such as depression or anxiety.
Received: 22 November 2018, Revised: 18 February 2019, Accepted: 18 March 2019, First published: 14 April 2019
Gesehen am 22.10.2019